A reassessment of the Bovidae (Mammalia) from the Nawata Formation of Lothagam, Kenya, and the late Miocene diversification of the family in Africa - (:unkn) unknown (My University, 2017)
The late Miocene Bovidae from the Nawata Formation of Lothagam were all assigned to modern tribes by Harris (2003), with the majority of specimens being referred to a species of Aepyceros, a genus that includes the modern impala. However, an alternative interpretation of the collection lessens the modern character of the faunal composition. Many of the identifications are revised: there might be a single species of Boselaphini, there is no evidence of Hippotragini, and Aepyceros is less common than previously thought. Two new genera, Afrotragus and Turkanatragus, are erected; together with an unnamed species and ‘Kobus’ laticornis Harris, 2003, they cannot easily be allocated to any existing tribe. These two new genera share long, slender, spiralled horn-cores, and it is conceivable that they belong to the same group, which might also include the ‘Prostrepsiceros’ from Sahabi, Libya, but does not seem closely related to Eurasian Prostrepsiceros. Along with sparser evidence from elsewhere in Africa, this strongly suggests that by the late Miocene, African Bovidae underwent a wider radiation than reflected in the tribes that survived into the Pliocene, showing that the crown groups very incompletely document the relatively recent past diversity of the family.
Keywords: African Research